О локально симметрической структуре, связанной с обобщенной левой три-тканью Бола Bl(p,q,q) - Толстихина, Г.А. (Інститут математики НАН України, 2009)
The generalized left Bol 3-web Bl(p,q,q) on a smooth manifold M, dimM = p+q, defined by a local smooth Bol quasigroup is considered. The symmetric space structure connected with the web Bl(p,q,q)is studied.